1997
DOI: 10.1016/s1074-7613(00)80406-9
|View full text |Cite
|
Sign up to set email alerts
|

Lymphoproliferation in CTLA-4–Deficient Mice Is Mediated by Costimulation-Dependent Activation of CD4 + T Cells

Abstract: CTLA-4-deficient animals develop a fatal lymphoproliferative disorder. The cellular mechanism(s) responsible for this phenotype have not been determined. Here, we show that there is a preferential expansion of CD4+ T cells in CTLA-4(-/-) mice, which results in a skewing of the CD4/CD8 T cell ratio. In vivo antibody depletion of CD8+ T cells from birth does not alter the onset or the severity of the CD28-dependent lymphoproliferative disorder. In contrast, CD4+ T cell depletion completely prevents all features … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
259
2
4

Year Published

1998
1998
2003
2003

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 373 publications
(274 citation statements)
references
References 61 publications
9
259
2
4
Order By: Relevance
“…Of note, we could also clearly observe negative regulation of Agspecific, preactivated CD8 ϩ T cells following CTLA-4/TCR coengagement using the 2C T cells. Thus, although recent studies have shown that CLTA-4 may not exert significant effects during primary CD8 ϩ T cell activation (52,65), our results and those of others (53,54) suggest that CTLA-4-mediated negative regulation of CD8 ϩ T cells may occur both indirectly, through inhibition of CD4 ϩ helper functions, and directly, through inhibition of expansion and cytokine production during secondary Ag encounters.…”
Section: Discussioncontrasting
confidence: 68%
“…Of note, we could also clearly observe negative regulation of Agspecific, preactivated CD8 ϩ T cells following CTLA-4/TCR coengagement using the 2C T cells. Thus, although recent studies have shown that CLTA-4 may not exert significant effects during primary CD8 ϩ T cell activation (52,65), our results and those of others (53,54) suggest that CTLA-4-mediated negative regulation of CD8 ϩ T cells may occur both indirectly, through inhibition of CD4 ϩ helper functions, and directly, through inhibition of expansion and cytokine production during secondary Ag encounters.…”
Section: Discussioncontrasting
confidence: 68%
“…The Frauwirth results are in keeping with those from Bachmann et al (27) who reported, while using a different CD8 ϩ TCR-transgenic mouse that CD152 played little, if any, role in regulating CD8 ϩ T cell responses. This contrasts with the in vivo observations for CD4 ϩ T cells (5,6), and with the fact that the predominant cell type that accumulates in the CD152 KO mouse is CD4 ϩ (28).…”
Section: Discussioncontrasting
confidence: 63%
“…CTLA-4-deficient mice develop more severe and systemic autoimmune diseases with early onset [13][14][15], whereas PD-1-deficient mice develop milder and organspecific autoimmune diseases with late onset [8,12]. These results suggest a minor impact of PD-1-mediated regulation in general lymphoid organs and a possible role for PD-1 in regulating immune responses in specific organs.…”
Section: Discussionmentioning
confidence: 87%
“…PD-1 is expressed on a subpopulation of thymocytes and on both T and B cells after antigenic stimulation [6, 10,11]. Although PD-1-deficient mice develop autoimmune diseases, such as lupus-like glomerulonephritis and dilated cardiomyopathy [8,12], these mice display markedly different phenotypes as compared with CTLA-4-deficient mice [13][14][15], suggesting a role for PD-1 distinct from that for CTLA-4. Two B7 family molecules have been identified as the ligands for PD-1: B7-H1/PD-L1 [16,17] (hereafter referred to as B7-H1) and B7-DC/PD-L2 [18,19] (hereafter referred to as B7-DC).…”
Section: Introductionmentioning
confidence: 99%